2020
DOI: 10.1002/anie.202001083
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimetallic Mixed‐Valent Molecular Precursors Containing Periodic Table Neighbors: Assignment of Metal Positions and Oxidation States

Abstract: A known trinuclear structure was used to design the heterobimetallic mixed‐valent, mixed‐ligand molecule [CoII(hfac)3−Na−CoIII(acac)3] (1). This was used as a template structure to develop heterotrimetallic molecules [CoII(hfac)3−Na−FeIII(acac)3] (2) and [NiII(hfac)3−Na−CoIII(acac)3] (3) via isovalent site‐specific substitution at either of the cobalt positions. Diffraction methods, synchrotron resonant diffraction, and multiple‐wavelength anomalous diffraction were applied beyond simple structural investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The foregoing study adds to the growing literature demonstrating the utility of MAD for oxidation state assessment of polynuclear transition metal clusters 10,[23][24][25][26][27][28] and presents the utility of absorption edge-generated 𝑓𝑓′ curves of mononuclear references. Furthermore, the complete overlay of the 𝑓𝑓′ traces for Cr2 and Cr3 of 3 and 5 despite a difference of two-electrons in the overall [Cr 3 ] oxidation state of 5 vs 3 ([Cr 3 ] 10+ vs [Cr 3 ] 8+ ) provides excellent evidence that this technique and data collection strategy is truly sensitive to the local metal oxidation state and unaffected by the aggregate oxidation state of the polynuclear core.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The foregoing study adds to the growing literature demonstrating the utility of MAD for oxidation state assessment of polynuclear transition metal clusters 10,[23][24][25][26][27][28] and presents the utility of absorption edge-generated 𝑓𝑓′ curves of mononuclear references. Furthermore, the complete overlay of the 𝑓𝑓′ traces for Cr2 and Cr3 of 3 and 5 despite a difference of two-electrons in the overall [Cr 3 ] oxidation state of 5 vs 3 ([Cr 3 ] 10+ vs [Cr 3 ] 8+ ) provides excellent evidence that this technique and data collection strategy is truly sensitive to the local metal oxidation state and unaffected by the aggregate oxidation state of the polynuclear core.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Recently, higher-resolution MAD studies have been conducted on synthetic manganese, iron, cobalt, and nickel-containing polynuclear clusters as well as on ironcontaining biological cofactors such as FeMoco. 10,[23][24][25][26][27] A previous study by our research group revealed how cluster features (e.g., metal primary coordination sphere, M-M bonding, mixed valency) in a triiron system impact MAD measurements, allowing us to correlate site specific redox information against bulk measurement techniques (e.g., 57 Fe Mössbauer, cyclic voltammetry). 28 Alongside the two imide structure types 2 and 3, a homovalent structural analogue of 2, ( tbs L)Cr 3 (CNBn) (4), and the further oxidized bisimide ( tbs L)Cr 3 (µ 3 -NPh)(NPh) (5) were also investigated using MAD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such molecules should efficiently release the products without impeding the continuation of the reaction. After a comprehensive search, we finally decided upon the alcohols based on four considerations: (1) they are able to tightly bind to the FeS x through −OH group 43 (e.g., used as passivation ligands to confine the crystal growth in the synthesis of FeS x nanocrystals); (2) the hydrogen bonding occurs between the alcohol and carboxylic complexes acts as a driving force to concentrate Cr(VI) complexes around S-ZVI; 32 (3) the alcohol is a relatively weak coordinating compound (relative to the bidentate carboxylic acid) which prefers to bind to the relatively electron-rich Fe centers, instead of the Cr species, avoiding uncontrollable and competing coordination processes toward the same metal atom; 44 (4) alcohols are a readily available reagent and the low cost makes them more interesting for large scale applications.…”
Section: Resultsmentioning
confidence: 99%
“…Great illustrations of this statement are analogous tetranuclear complexes with an A:M = 1:1 ratio, [A 2 M 2 L 6 ] (A = Li, Na; M = transition metal) [27,31], where Na not only requires an additional coordination by THF molecules but also changes the whole ligand distribution within the heterometallic assembly. Even more, in none of the heterometallic structures [1,15,27,32] were we able to replace Na for Li, and vice versa, without changing the structure itself, as well as the connectivity pattern. The sole exception is the family of 1D polymeric chain complexes [AML 3 ] ∞ (L = acac = acetylacetonate or hfac = hexafluoroacetylacetonate) that accommodate both Li [31] and Na [33] as 6-coordinated "naked" ions.…”
Section: Introductionmentioning
confidence: 93%
“…It should be noted that no single-source precursor has been advanced for the preparation of the above-mentioned SMO cathode materials. While we have recently introduced [15] a broad family of precursors for layered P2-Na x MO 2 oxides, the latter did not include Mn compounds. That said, the multi-source precursor approach has been successfully applied [16][17][18] for the hydrothermal preparation of Na 4 Mn 9 O 18 , though the product was found to be not a phase-pure.…”
Section: Introductionmentioning
confidence: 99%